Analysis of Financing Strategy in Optimizing The Concept of Green Finance (Case Study at Bankaltimtara Syariah, Berau Regency) - Endah Susanti (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2022)
Sustainable Finance is an issue whose discussion continues to heat up from time to time, not only because of the targets that some G20 member countries consider pretty ambitious but also the urgency to implement commitments in controlling climate damage. This issue can lead to a more severe impact on social and economic life if not immediately addressed. Green Finance is based on the Triple Bottom Line, namely Profit, People and Planet, which focuses on optimizing economic factors and pays attention to sustainability and sustainability of environmental factors. The community demands that companies follow the concept of Green Finance to achieve environmental improvements that go hand in hand with the development of the economy. This study aimed to determine the application of Green Finance to finance the Bankaltimtara Syariah Berau Branch and to optimize existing Green Finance using SWOT analysis. The study used a descriptive qualitative approach. The object of the research was taken at Bankaltimtara Syariah, Berau Regency. The data analysis technique uses data presentation analysis methods, data reduction, data display, conclusion drawing and verification. The results show that the application of Green Finance at the Bankaltimtara Syariah Berau Branch aims to improve the economic level of customers and emphasizes social care and environmental analysis following the AMDAL. Bankaltimtara Syariah Berau Branch has the potential to become a bank that maintains economic and natural stability and fulfils customer needs. Bankaltimtara Syariah Berau Branch seeks to optimize by balancing the aspects of people (society), planet (environment), and profit (economy), strict in releasing financing, and Account Officer who is observant in providing financing and providing comfort to financing customers.